(untitled) (Research, Society and Development, 2022)
This study has the objective to analyze the profile of Breastfeeding Support Rooms in the southern states of Brazil to identify data on their use and monitoring, as well as challenges and benefits to their implementation. Descriptive cross-sectional study was carried out, and an online questionnaire was applied to supervisors from certified companies. All analyses were performed with the Statistic v.10.0 (Statsoft R) software. Sixteen certified Breastfeeding Support Rooms from 12 companies participated in the study. The median of women who used Breastfeeding Support Rooms 3 (1-28) was about five times lower than the median of employees on maternity leave 17 (1-184). The main challenges Breastfeeding Support Rooms face relate to the standardization of internal processes and their infrequent use, while their benefits include the encouragement of breastfeeding and the appreciation of working mothers. This is the first study that analyzes the profiles of Breastfeeding Support Rooms in Brazil. More benefits than challenges were found in companies that implemented Breastfeeding Support Rooms, our results identified important challenges for broadening the program.